2015
DOI: 10.1007/s10120-015-0580-2
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of adjuvant chemotherapy with docetaxel, capecitabine, and cisplatin in patients with curatively resected stage IIIB–IV gastric cancer

Abstract: Objective Postoperative chemotherapy with S-1 or capecitabine plus oxaliplatin is a standard treatment for resectable gastric cancer (GC). However, survival outcomes of stage IIIB-IV (M0) GC cases are still poor. We investigated the efficacy and safety of docetaxel, capecitabine, and cisplatin (DXP) in patients with stage IIIB-IV GC. Methods This was a single-arm phase 2 study that included patients with stage IIIB-IV GC who underwent D2 gastrectomy. Patients received six cycles of docetaxel [60 mg/m 2 on day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…conducted a phase II clinical study about docetaxel, capecitabine, and cisplatin (DXP) triplet chemotherapy in advanced gastric cancer. e result showed that DXP was safe and might be better in terms of recurrence-free survival (RFS) [16,20]. Swiss group for clinical cancer research conducted a randomized phase II clinical trial to make a comparison between docetaxel + cisplatin + 5FU (DCF) and ECF to see which would be most promising according to the overall response rate (ORR) [17,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…conducted a phase II clinical study about docetaxel, capecitabine, and cisplatin (DXP) triplet chemotherapy in advanced gastric cancer. e result showed that DXP was safe and might be better in terms of recurrence-free survival (RFS) [16,20]. Swiss group for clinical cancer research conducted a randomized phase II clinical trial to make a comparison between docetaxel + cisplatin + 5FU (DCF) and ECF to see which would be most promising according to the overall response rate (ORR) [17,21].…”
Section: Discussionmentioning
confidence: 99%
“…e influence of neoadjuvant chemotherapy on the operative morbidity and mortality is another critical problem due to the degree of toxicity [20,24]. e most noticeable postoperative complications are surgical site infections including wound infections and intra-abdominal abscess, followed by anastomotic leakage [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…The ACTS-GC trial (24) and CLASSIC trial (25) proved the efficacy of S-1 and XELOX regimens as adjuvant chemotherapy for East Asian patients with gastric cancer who received curative surgery with D2 lymphadenectomy. Moreover, taxane has been used extensively as part of neoadjuvant chemoradiotherapy (26), chemotherapy (27)(28)(29), and adjuvant chemotherapy regimens (30,31) due to its high efficacy as palliative chemotherapy for advanced gastric cancer (23). Our department (30) has previously reported a study of 32 patients with gastric cancer who received the DCF regimen as adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 2-year disease-free survival rate was lower than the 3-year disease-free survival rate in the ACTS-GC trial (72.2%) and the CLASSIC trial (74.0%), the patients in our study generally harbored more advanced disease, as nearly 70% of the patients were diagnosed with stage III disease. Yoon et al (31) administered the docetaxel + capecitabine + cisplatin (DXP) regimen as adjuvant chemotherapy to patients with stage IIIB-IV disease according to the AJCC 6.0; the results showed that the median relapse-free survival was 26.9 months, and the 5-year relapse-free survival rate was 39.1%. Hence, in this study, we used taxane-based chemotherapy as modified adjuvant chemotherapy after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have described the effectiveness of DCX for unresectable gastric cancer[ 10 , 16 ], as preoperative chemotherapy[ 17 ], as adjuvant chemotherapy[ 18 ] and as perioperative chemotherapy[ 12 ]. These reports indicate that DCX is highly effective but also rather toxic, particularly in hematologic respects.…”
Section: Discussionmentioning
confidence: 99%